Modelo de gestión por procesos para la clínica Jerusalem ubicada en la parroquia Chillogallo al sur de Quito. - Salazar Veira, William Efrén (2011)
The overall objective of this document is "Structure and operationalize the Model Process Management to ensure optimal performance of the resources of the Jerusalem clinic that is located in the Parish Chillogallo south of Quito". The main problem with the Jerusalem clinic is poor attention to enter a patient facilities among others, by the delay in care, which has been forced to take control measures to improve the process of care.